The Relationship Between Electrodiagnostic Findings and the DN4 Questionnaire in Patients with Carpal Tunnel Syndrome. Issue 1 (March 2013) - Turgut, Selin Turan; İçağasıoğlu, Afitap; Selimoğlu, Esra; Atlığ, Raife Şirin; Adatepe, Turgut; Mesci, Erkan
<x xml:space="preserve">Abstract</x> Objective We aimed to identify relationships between findings of electrodiagnostic testing [electromyography [EMG]] and the Douleur Neuropathique 4 Questions [DN4] questionnaire in patients that presented to our physical therapy and rehabilitation department with carpal tunnel syndrome [CTS]. Methods In our study, patients diagnosed with CTS by EMG were included. Demographic data of the patients were acquired and analyzed. The EMG findings were recorded. The Boston Carpal Tunnel Syndrome Questionnaire [BCTSQ] was used for assessment of the patients' subjective complaints. The presence of neuropathic pain was assessed by the DN4 questionnaire. Results Recruited were 132 hands of 72 [66 female and 6 male] with CTS. The severity of the CTS and the BCTSQ scores exhibited a statistically significant relationship [P<0.05]. Although there was a statistically significant relationship between severity of the EMG findings and two parameters [hypoesthesia to prick and brushing] of the DN4 questionnaire [P<0.05], there was no significant relationship [P>0.05] between total DN4 score and the severity of the EMG findings. Discussion In the literature, there are few studies that investigated the relationship between EMG findings and neuropathic pain scales in patients with CTS, and the results have been controversial. In our study, even though EMG findings correlated with subjective complaints, there was no correlation between EMG findings and neuropathic pain. We believe that further controlled studies with larger samples are indicated.